1990
DOI: 10.1111/j.1365-246x.1990.tb05679.x
|View full text |Cite
|
Sign up to set email alerts
|

Wave propagation in laterally heterogeneous layered media

Abstract: This paper derives a solution of the seismic response of an acoustic medium with 2-D geometry using Kirchhoff's representation of the wavefield. The medium can be composed of several layers, separated by curved interfaces.The difference between the approach presented here and other Kirchhoff-type solutions of the multilayer case is that we take care of all diffractive effects during wave propagation, including those during transmission from source to reflector and from reflector to receiver.A crucial point in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The IBEM results were obtained by adapting the formulation of SÁ NCHEZ-SESMA andCAMPILLO (1991) andPEDERSEN et al (1996) to an explosion in the model geometry shown in Figure 4b. In Figure 5b, we compare the zero-offset 2 Hz wave forms computed by these two methods and by the WKBJ technique used in the previous example (see also WENZEL et al, 1990). It is apparent from Figure 4, that the performance of KH is satisfying near the caustic where the ART is not valid.…”
Section: Reflection Problemmentioning
confidence: 93%
See 3 more Smart Citations
“…The IBEM results were obtained by adapting the formulation of SÁ NCHEZ-SESMA andCAMPILLO (1991) andPEDERSEN et al (1996) to an explosion in the model geometry shown in Figure 4b. In Figure 5b, we compare the zero-offset 2 Hz wave forms computed by these two methods and by the WKBJ technique used in the previous example (see also WENZEL et al, 1990). It is apparent from Figure 4, that the performance of KH is satisfying near the caustic where the ART is not valid.…”
Section: Reflection Problemmentioning
confidence: 93%
“…Next, the components (8) are evaluated upon use of the well-known elementary source solutions whenever possible. In more complicated models, these components are expanded into the WKBJ series (SINGH and CHAPMAN, 1988;WENZEL et al, 1990). By putting the source location x% into a complex space, we may also construct an analytical extension of the diverging wave propagating away from this source (FELSEN, 1984;WU, 1985).…”
Section: Remarks On the Numerical Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…which are the well-known Kirchhoff-Helmholtz integrals ͑Morse and Feshbach, 1953;Berkhout, 1985͒, with many applications in seismic modeling ͑Frazer and Sen, 1985;Hill and Wuenschel, 1985;Wenzel et al, 1990;Druzhinin et al, 1998͒. Equation 63 is the generalization of the Kirchhoff-Helmholtz integral for any of the wave phenomena considered in this paper.…”
Section: Forward Wavefield Extrapolationmentioning
confidence: 99%